Telemedicine for rotator cuff syndrome: Asynchronous exercise and remote follow-up in a randomized controlled study - Selkin Yilmaz Muluk; Nazlı Olcucu; Ozlem El (PLoS ONE, 2026)
Introduction Rotator cuff syndrome (RCS) is a common musculoskeletal condition that requires rehabilitation. Telemedicine involving asynchronous exercise video and remote follow-up has emerged as a potential alternative to conventional in-person rehabilitation, offering advantages in accessibility and cost-effectiveness. This study aimed to evaluate the effectiveness of telemedicine compared to conventional methods in the rehabilitation of RCS. Methods This randomized controlled trial was conducted at a public hospital physiatry clinic between November 2023 and June 2024. The telemedicine group (TG) received asynchronous exercise videos and remote video-call follow-ups; the control group (CG) received illustrated exercise brochures and in-person follow-ups. Outcomes were assessed at baseline, 15 th day, and 6 th month. The primary outcomes were pain (measured using the Visual Analog Scale, VAS) and functional levels (assessed using the Quick Disabilities of Arm, Shoulder, and Hand, QuickDASH). Secondary outcomes included exercise adherence, satisfaction, and travel burden. Data were analyzed using linear mixed-effects models. Results Trial included 90 patients (mean age 51.19 ± 7.07 years), randomly assigned to TG (n = 45) or CG (n = 45). Both groups demonstrated within-group improvements in VAS (mean change −1.88 [95% CI −2.56 to −1.20]) and QuickDASH (−15.6 [95% CI −21.0 to −10.2]) scores from baseline to 15 th day (p < 0.001) and in VAS from baseline to 6 th month (−4.82 [95% CI −5.50 to −4.13], p < 0.001). No between-group differences were found in pain reduction at 15 th day (estimate = −0.27, 95% CI −1.44 to 0.89, p = 0.645) or at 6 th month (estimate = −0.40, 95% CI −1.57 to 0.77, p = 0.499), nor in functional improvement at 15 th day (estimate = −2.68, 95% CI −12.90 to 7.57, p = 0.607). The TG demonstrated higher exercise adherence (p = 0.027) and satisfaction (p < 0.001). Based on predefined minimal clinically important difference thresholds, all group differences fell within non-inferiority margins. The cost-effectiveness of telemedicine was 266.4 km and 1325.6 minutes saved per unit of VAS, and 11.34 km and 56.41 minutes saved per unit of QuickDASH improvement. Conclusion Telemedicine is a viable alternative to traditional management of RCS, providing comparable pain relief, functional outcomes, and reduced travel burden. Future studies should assess long-term effects and broader populations.